Analisis Pesan Iklan Pertamina Edisi “Gerakan Kebaikan Lampaui Batasan” - Ana Silviatus Zahrah (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the meaning of the message in Pertamina’s advertisement “Gerakan Kebaikan Lampaui Batasan” (Movement of Kindness Beyond Limits) using Charles Sanders Peirce’s semiotic theory, which consists of three main elements: representamen (sign), object, and interpretant. The advertisement features various social and visual actions that reflect the spirit of kindness, inclusivity, and care for others. Through the analysis of visual signs such as gestures, facial expressions, and symbols of solidarity, the study reveals that Pertamina seeks to build a positive corporate image through a strong humanitarian message. The signs used in the advertisement convey the importance of empathy, social collaboration, and respect for diversity. The advertisement not only promotes the brand but also functions as an educational tool, instilling moral and social values in the audience. By using Peirce’s semiotics, this research uncovers the deeper meanings embedded in the advertisement’s visual elements, demonstrating how the company connects with society through values that transcend business objectives.